Data governance activities: an analysis of the literature. (10th June 2016) - Alhassan, Ibrahim; Sammon, David; Daly, Mary
Abstract: Data governance is an emerging subject in the information system (IS) field. In recent years, the volume of data used within organisations has increased dramatically, playing a critical role in business operations. This paper explores the current literature on data governance and is intended to provide a comprehensive analysis of the activities involved in data governance. Six major academic databases in the IS domain were searched using key terms to identify and analyse material reflecting the current state of knowledge. A systematic procedure was developed to identify 31 papers that explicitly mention data governance activities. Open coding techniques were applied to conduct content analysis, resulting in 110 data governance activities across five decision domains of the data governance framework. These data governance activities are understood as: 'action' plus 'area of governance' plus 'decision domain' e.g. (define data policies for data quality). Our analysis shows a high volume of data governance activities associated with the 'defining' action of the areas of governance across the decision domains with a lack of reported on the 'implementing' and 'monitoring' actions.